2016
DOI: 10.1002/glia.23030
|View full text |Cite
|
Sign up to set email alerts
|

Glial Na+‐dependent ion transporters in pathophysiological conditions

Abstract: Sodium dynamics are essential for regulating functional processes in glial cells. Indeed, glial Na+ signaling influences and regulates important glial activities, and plays a role in neuron-glia interaction under physiological conditions or in response to injury of the central nervous system (CNS). Emerging studies indicate that Na+ pumps and Na+-dependent ion transporters in astrocytes, microglia, and oligodendrocytes regulate Na+ homeostasis and play a fundamental role in modulating glial activities in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 227 publications
(342 reference statements)
1
36
1
2
Order By: Relevance
“…This makes NCX instrumental for shaping Ca 2+ and Na + signalling and thus affecting the excitation-contraction coupling, neurotransmitters transport, mitochondrial bioenergetics and neuron-glia interactions among many other (Bers, 2002; Kirischuk et al , 2012; De Stefani et al , 2016; Parpura et al , 2016; Robinson & Jackson, 2016). On the other hand, small anomalies in allosteric regulation of NCX or coupled ion-transport systems may end-up with devastating outcomes (Wagner et al , 2015; Boscia et al , 2016). For example, Na + -driven uptake of neurotransmitters (e.g., GABA or glutamate) elevates [Na + ] i , thus promoting Ca 2+ entry through NCX operating in the reverse mode and increase [Ca 2+ ] i with ensuing excitotoxicity (Kirischuk et al , 1997; Boscia et al , 2016; Rose & Verkhratsky, 2016).…”
Section: Sodium-calcium Exchanger: the Key Element Of Na+/ca2+ Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes NCX instrumental for shaping Ca 2+ and Na + signalling and thus affecting the excitation-contraction coupling, neurotransmitters transport, mitochondrial bioenergetics and neuron-glia interactions among many other (Bers, 2002; Kirischuk et al , 2012; De Stefani et al , 2016; Parpura et al , 2016; Robinson & Jackson, 2016). On the other hand, small anomalies in allosteric regulation of NCX or coupled ion-transport systems may end-up with devastating outcomes (Wagner et al , 2015; Boscia et al , 2016). For example, Na + -driven uptake of neurotransmitters (e.g., GABA or glutamate) elevates [Na + ] i , thus promoting Ca 2+ entry through NCX operating in the reverse mode and increase [Ca 2+ ] i with ensuing excitotoxicity (Kirischuk et al , 1997; Boscia et al , 2016; Rose & Verkhratsky, 2016).…”
Section: Sodium-calcium Exchanger: the Key Element Of Na+/ca2+ Signalmentioning
confidence: 99%
“…On the other hand, small anomalies in allosteric regulation of NCX or coupled ion-transport systems may end-up with devastating outcomes (Wagner et al , 2015; Boscia et al , 2016). For example, Na + -driven uptake of neurotransmitters (e.g., GABA or glutamate) elevates [Na + ] i , thus promoting Ca 2+ entry through NCX operating in the reverse mode and increase [Ca 2+ ] i with ensuing excitotoxicity (Kirischuk et al , 1997; Boscia et al , 2016; Rose & Verkhratsky, 2016). Moreover, when E NCX and E m are close, any small changes in the extracellular [K + ] (for example released from neurones during repolarisation) may change membrane potential thus affecting the rates and directionality of NCX.…”
Section: Sodium-calcium Exchanger: the Key Element Of Na+/ca2+ Signalmentioning
confidence: 99%
“…NHE1 plays an important role in regulating microglial intracellular pH (pH i ) homeostasis, their activation, and migration (Boscia et al, 2016; Liu et al, 2010; Shi et al, 2013; Zhao et al, 2016; Zhu et al, 2016). In particular, NHE1 maintains optimal pH i to support NADPH oxidase (NOX) function during microglial activation (Lam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting finding of our study is that D-Asp exposure significantly and dose-dependently upregulated the transcripts levels of the Na + /Ca 2+ exchanger NCX3, a plasma membrane component of myelin membranes (Gopalakrishnan et al, 2013) whose increased expression and activity has been shown to be essential for controlling [Na + ] i and [Ca 2+ ] i in OPC during differentiation and myelin synthesis (Boscia et al, 2012(Boscia et al, , 2016aFriess et al, 2016). Consistent with the boosting effects of D-Asp on OPC development through a mechanisms involving the activation of both glutamate receptors and NCX3 exchangers, we found that the upregulation of NCX3 transcripts following D-Asp exposure was significantly prevented by the NMDA receptor blocker and the pharmacological blockade of NCX3 exchanger significantly prevented myelin marker increase after D-Asp exposure.…”
Section: Discussionmentioning
confidence: 66%
“…In this regard, glutamate signaling through a-amino-3hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPA) and N-Methyl-D-Aspartate (NMDA) receptors has garnered the main interest as inductive signal prompting OPC to differentiate and remyelinate (Yuan et al, 1998;Li et al, 2013;Fannon et al, 2015;Gautier et al, 2015). In line, mounting evidence suggests that the activation of Ca 2+ -dependent pathways through glutamate receptors or the Na + /Ca 2+ exchanger NCX3 may influence oligodendrocyte maturation, myelin synthesis, and remyelination processes (Boscia et al, 2012(Boscia et al, , 2016aMartinez-Lozada et al, 2014;Casamassa et al, 2016;Friess et al, 2016).…”
Section: Introductionmentioning
confidence: 99%